1977
DOI: 10.1111/j.1399-6576.1977.tb01200.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Effects of Neuroleptanaesthesia

Abstract: Oxygen uptake, cardiac output, stroke volume and arterial and central blood pressures were measured before and after induction of neuroleptanaesthesia in 27 subjects. Nine were elderly patients operated on for obliterative arteriosclerotic disease, and the other 18--nine elderly and nine younger patients--underwent operation for varicose veins. Cardiac output, stroke volume and systolic arterial blood pressure decreased significantly with a corresponding decrease in oxygen uptake. The changes were most pronoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…The values returned to control levels during steady-state anaesthesia. Before intubation, SVR decreased significantly, presumably due to the alpha-blocking effrct of droperidol (YELNOSKY et al 1964), a finding in contrast with those observed by PRYS-ROBERTS et al (1971) andBRISMAR et al (1977). Like these authors we found a fall in MAP during steady-state (I-IV) .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The values returned to control levels during steady-state anaesthesia. Before intubation, SVR decreased significantly, presumably due to the alpha-blocking effrct of droperidol (YELNOSKY et al 1964), a finding in contrast with those observed by PRYS-ROBERTS et al (1971) andBRISMAR et al (1977). Like these authors we found a fall in MAP during steady-state (I-IV) .…”
Section: Discussionsupporting
confidence: 56%
“…Neurolept anaesthesia is well tolerated by patients with various cardiovascular diseases (NILSSON & JANSSEN 1961, PRYS- ROBERTS et al 1971, STOELTING et al 1975, BRISMAR et al 1977.…”
Section: After Halothane Inhalation (Sorensen and Jacobsen 1977)mentioning
confidence: 99%
“…The patients selected for this study all had impaired left ventricular function, as their PCWP increased more than 0.8 kPa (mean 1.6 to 4.1 kPa) during an exercise test with a moderate work load, indicating the need for a higher left ventricular filling pressure in response to a submaximal work load. Before intubation, SVR decreased significantly, presumably due to the alpha-blocking effect of droperidol (YELNOSKY et al 1964), a finding in contrast with those observed by PRYS-ROBERTS et al (1971) andBRISMAR et al (1977). During the exercise test an increased workload was imposed on the heart, but no similar increased workload was seen during induction of neurolept anaesthesia in the present study.…”
Section: Discussioncontrasting
confidence: 82%
“…There is ample evidence that tissue oxygen demand is the major factor regulating cardiac output in conscious man (GUYTON et al 1964, BEVEGARD & SHEPHERD 1967. Previous investigations have shown that the reduced cardiac output found during both halothane and neurolept anaesthesia is often related to a diminished tissue oxygen demand (SEVERINGHAUS & CULLEN 1958, THEYE 1967, BRISMAR et al 1977). In the present study, cardiac output decreased proportionally to the reduced oxygen uptake, as AVD remained unchanged.…”
Section: Discussionmentioning
confidence: 99%